N4-Cytosine DNA Methylation Is Involved in the Maintenance of Genomic Stability in Deinococcus radiodurans - Li, Shengjie; Cai, Jianling; Lu, Huizhi; Mao, Shuyu; Dai, Shang; Hu, Jing; Wang, Liangyan; Hua, Xiaoting; Xu, Hong; Tian, Bing; Zhao, Ye; Hua, Yuejin (Frontiers in Microbiology, 2019)
DNA methylation serves as a vital component of restriction-modification (R-M) systems in bacteria, where it plays a crucial role in defense against foreign DNA. Recent studies revealed that DNA methylation has a global impact on gene expression. Deinococcus radiodurans, an ideal model organism for studying DNA repair and genomic stability, possesses unparalleled resistance to DNA-damaging agents such as irradiation and strong oxidation. However, details on the methylomes of this bacterium remain unclear. Here, we demonstrate that N4-cytosine is the major methylated form (4mC) in D. radiodurans. A novel methylated motif, ‘C4mCGCGG’ was identified that was fully attributed to M.DraR1 methyltransferase. M.DraR1 can specifically bind and methylate the second cytosine at N4 atom of ‘CCGCGG’ motif, preventing its digestion by a cognate restriction endonuclease. Importantly, cells deficient in 4mC modifications displayed higher spontaneous mutation frequency and enhanced DNA recombination and transformation efficiency. Moreover, genes involved in the maintenance of genomic stability were differentially expressed in conjunction with the loss of M.DraR1. This study provides evidence that N4-cytosine DNA methylation contributes to genomic stability of D. radiodurans and lays the foundation for further research on the mechanisms of epigenetic regulation by R-M systems in bacteria.